REVIEW OF THE LAST POETRY COLLECTION, „BLACK ARIES“ BY BLAZE KONESKI - Samardzieva, Bojana (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
This paper is an overview of the last poetry collection of Blaze Koneski. It is about the poetic collection „Black Aries“, published only a few months before his death. Although he planned to stop writing, the influx of verses made him create his last piece. Koneski gives a symbolic title to his collection, trying from the beginning to present his view and express his feelings. The overall poetry of this collection is a set of intertwined emotions: sadness, loneliness, nostalgia, turmoil. He uses short, but well-thought words, which may seem poor, but they are with deep meaning. But also in his poetry, Koneski expresses his calmness and his anticipation of the end as death constantly lurks over his pen. He himself feels the end approaching, so he finalized one era, epoch, as it befits such a great poet.Keywords: last words; forgiveness; pain; sadness; death.